Effects of Rice Husk and Rice Straw Hydrochar as Soil Amendment - Adilah Ahmad Asmadi; Pramila Tamunaidu; Goto Masafumi; Utsumi Motoo (Chemical Engineering Transactions, 2023)
Biomass wastes, such as agricultural residues from rice field are generated in a large amount. Hydrothermal carbonization (HTC) treatment can convert biomass wastes into value-added product known as hydrochar, which gained researchers interests for various environmental applications. However, recent studies have shown inconsistent results for the use of hydrochar on crop production and soil improvement. Thus, the aim of this study is to understand the characteristics and potential use of rice husk and rice straw hydrochar as soil amendment. Two types of hydrochar (RHH: rice husk hydrochar, and RSH: rice straw hydrochar) produced using HTC at a pressure of 1.6 MPa, temperature at 160 – 180 °C, and reaction time of 30 min, were used to conduct pot experiment. Nutrients and morphological study of hydrochar and its raw biomass were analyzed. Five treatments (0 % hydrochar as control, 1 % RHH, 10 % RHH, 1 % RSH, and 10 % RSH (w/w)) were applied in commercial garden soil to observe the effects on soil pH and Spinach plant growth. The result from this study shows that HTC have significant effects on the hydrochar properties. The hydrochars have coarser surface and several microstructures formed on the surface. HTC significantly decreased pH, increased moisture content, and altered the nutrient compositions of the biomass. Pot experiment results showed that all hydrochar-amended treatments decreased soil pH below optimal pH of 6.0, which causes the decreased plant biomass by 60 – 67 % compared to control. This shows that these hydrochars are useful as soil amendment for dry degraded soils with pH =8. Further research is needed to reveal the mechanisms and potential modification required before using the hydrochar as soil amendment.